A descriptive review of the role of exogenous bovine somatotropin on milk secretion mechanisms at different stages of lactation in crossbred Holstein cattle in the tropics - Narongsak Chaiyabutr; Somchai Chanpongsang; Sumpun Thammacharoen (Veterinary Integrative Sciences)
This review aims to better understand the regulation of milk yield in response to the prolonged administration of recombinant bovine somatotropin (rbST) in 87.5% crossbred Holstein cattle in the tropics. Prolonged administration of rbST at different stages of lactation is associated with an increase in milk yield, which correlates with an increase in milk lactose yield and mammary glucose uptake, due to an increase in mammary blood flow. Lactose synthesis is up-regulated in response to the administration of rbST. The glucose taken up by the mammary gland in early lactation increases flux through the lactose synthesis and pentose phosphate pathways, leading to significant increases in NADPH formation for fatty acid synthesis during rbST administration. The incorporation of glucose carbon into milk increases milk citrate and triacylglycerol concentrations but not milk lactose as lactation advances under rbST treatment. The stimulatory effect of rbST on milk yield would be transiently and significantly increased in early lactation and decrease in late lactation, even though there is a high level of udder blood flow. With prolonged administration of rbST, the regulation of biosynthetic capacity within the mammary gland would be influenced more by intra-mammary factors than by systemic factors. As lactation advances, a smaller proportion of glucose would be metabolized for lactose synthesis, with more being metabolized via the Embden-Meyerhof pathway and the tricarboxylic acid cycle.